The Value Chain Analysis and Strategies for the Development of Ginger Farming in Semarang Regency - Avi Budi Setiawan; Ririn Nur Fadillah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2021)
Ginger is a biopharmaceutical commodity which has a high economic value. However, a long ginger trading system makes the position of farmers as the producer have low bargaining power. The purpose of this research was to analyze the value chain and develop strategies for increasing ginger commodities in Semarang Regency. The method used in this research was quantitative descriptive using primary data with the number of respondents as many as 98 ginger farmers, 2 collectors, 2 wholesalers, 2 retailers and 6 key persons. The variables in this research included value chains, marketing margins, cultivation, post-harvest, marketing, institutions and policies. The analysis tools used were Value Chain Analysis and Analytic Hierarchy Process (AHP). The results showed that (1) Ginger farming in Semarang Regency was profitable with an average production or r/c ratio of 5,1. (2) There were three patterns of ginger trading in Semarang Regency, and their selection depended on the amount of production, transportation, facilities and capabilities owned by farmers. (3) The most prioritized criteria in the strategy of developing ginger farming in Semarang Regency covered marketing, cultivation, policy, harvesting and institutional aspects. Regarding these findings, suggestions or recommendations are given as follows: (1) carrying out harvesting process such as ginger powder independently. (2) forming ginger farmer groups to shorten the marketing chain of ginger, and increase the income of ginger farmers. (3) performing innovative digital marketing strategies.